(3eSfO GdEeGe CMeO Hf MfHds - (3GdTjHGfj, GdeQhRj, GdHZOGOj, CHh YHO Gddg, CMeO Hf eMeO Hf MfHd, J (B241(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; CNHQfG GdTjN CHh GdbGSe gHI Gddg Hf eMeO Hf YHO GdhGMO Hf CMeO Hf GdMUjf GdTjHGfj bQGAI Ydjg (B- (3hCfG CSeY (B- (3aCbQ Hg bGd (B: (3MOKfG CHh Ydj GdMSf Hf Ydj Hf eMeO GdJejej GdhGYX hjYQa HGHf GdePgH , bQGAI ef CUd SeGYg , bGd (B: "(3CfG(B" (3CHh HcQ CMeO HfYaQ Hf MeOGf Hf eGdc GdbWjYj , bQGAI Ydjgs
(3BNQgG (B:s
(3Yf GdMce , Yf ebSe , Yf GHf YHGS , Cf QShd Gddg Udi Gddg Ydjg hSde bOe VYaI Cgdg ef GdeROdaI Hdjd , aLYd jhUjgf (B( (3cPG (B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 203s
(3eYLe GdeDdajf (B1 / 261s
(3cTa GdXfhf (B2 / 1680s
(3JGQjN GdESdGe (B/ (3hajGJ (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs